2022
DOI: 10.5089/9798400215421.001
|View full text |Cite
|
Sign up to set email alerts
|

Macroprudential Regulation and Sector-Specific Default Risk

Abstract: for the authorization of using their database and in particular, Duan Jin-Chuan, Zhang Jiayu and Thibaud Jack Limandat. We are also grateful for excellent comments Nina Biljanovska, Romain Bouis and Selim Elekdag. We thank the participants at McGill University and at Université Catholique de Louvain for their questions and comments. Jean-Charles Wijnandts gratefully acknowledges research support from the Belgian Fonds National de la Recherche Scientifique (F.R.S. -FNRS) under the ASP grant (grant code: FC 7207… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Their findings were in line with the study by Kim and Mehrotra (2017) in the case of the Asia-Pacific region, using structural panel vector autoregressions. Boar et al (2017) and Kim and Mehrotra (2017) were further supported by Belkhir et al (2022), who studied the same subject matter during the banking crises in a panel of 134 countries, covering the time span 2000-2017, using the Early Warning System model. A contradiction emerged following the study by Andries and Melnic (2019) in a panel of 61 countries over the period 2000-2015, using System-GMM.…”
Section: The Empirical Analysis Of Macroprudential Policies and Econo...mentioning
confidence: 90%
See 1 more Smart Citation
“…Their findings were in line with the study by Kim and Mehrotra (2017) in the case of the Asia-Pacific region, using structural panel vector autoregressions. Boar et al (2017) and Kim and Mehrotra (2017) were further supported by Belkhir et al (2022), who studied the same subject matter during the banking crises in a panel of 134 countries, covering the time span 2000-2017, using the Early Warning System model. A contradiction emerged following the study by Andries and Melnic (2019) in a panel of 61 countries over the period 2000-2015, using System-GMM.…”
Section: The Empirical Analysis Of Macroprudential Policies and Econo...mentioning
confidence: 90%
“…This section will provide a quick overview of the literature on the impact of macroprudential policy on economic growth. In the literature, a negative impact of macroprudential policy on economic growth has been evidenced (Boar et al 2017;Kim and Mehrotra 2017;Alin and Florentina 2019;Belkhir et al 2022), while few have shown the positive effects (Andries and Melnic 2019). Boar et al (2017) documented that macroprudential policies are detrimental to growth in a panel of 64 developing and developed countries using the GMM.…”
Section: The Empirical Analysis Of Macroprudential Policies and Econo...mentioning
confidence: 99%
“…Looking forward, however, fast-growing and evolving fintech will have a greater effect on financial stability and consequently important policy implications, especially with increase in adaptation by large established institutions and big-tech companies. Not only do fintech firms tend to take on more risks themselves, but they also exert pressure on traditional financial institutions by degrading profitability, loosening lending standards improperly, and increasing risk-taking in operations and transactions (Cornaggia et al 2018;FSB 2019;Baba et al 2020;An and Rau 2021;Wang et al 2021;Ben Naceur et al 2023;Haddad and Hornuf 2023). Furthermore, as shown by recent developments, systemic financial risks can arise from institutions that individually Fig.…”
Section: Introductionmentioning
confidence: 99%